Meeting Island Dwarfs and Giants of the Cretaceous – The Hațeg Country UNESCO Global Geopark, Romania - Zoltán Csiki-Sava; Alexandru Andrășanu (Geoconservation Research, 2021)
We review here key geological heritage elements of the Hațeg Country UNESCO Global Geopark (Southern Carpathians, western Romania) represented by latest Cretaceous continental vertebrate fossils and the sedimentary rocks enclosing them. Based on available geological and paleontological evidence, these animals were living on a tropical island. This paleogeographic setting led to the development of some unusual paleobiological traits including dwarfing of the dinosaurs, high levels of endemism, relictual characteristics, as well as uniquely derived anatomical, developmental, metabolic and/or sensory features. These unique characteristics led to the establishment of the Hațeg Country UNESCO Global Geopark over a decade ago. Recently, the Geopark implemented several projects including specific ‘Dinosaur Island’-related thematic trails and visits to key geoheritage elements. We focus on four key fossiliferous areas of the Geopark, highlighting the most important geoheritage elements of each, as well as the most significant geoproducts created based on these particular elements.